My brief history [compact disc, unabridged] - Hawking, Stephen, 1942-2018 (Random House Audio, 2013)
Recounts Stephen Hawking's improbable journey, from his postwar London boyhood to his years of international acclaim and celebrity. Writing with characteristic humility and humor, Hawking opens up about the challenges that confronted him following his diagnosis of ALS at age 21. Tracing his progress as a thinker, he explains how the prospect of an early death urged him onward through numerous intellectual breakthroughs, and talks about the genesis of his masterpiece A Brief History of Time.